Aphicidal Activity of Surfactants Produced by Bacillus atrophaeus L193 - Rodríguez, Miguel; Marín, Ana; Torres, Marta; Béjar, Victoria; Campos, Mercedes; Sampedro, Inmaculada (Frontiers in Microbiology, 2018)
The biosurfactants produced by Bacillus atrophaeus L193 was examined by their use in the control of the aphid Rhopalosiphum padi in order to suggest a friendly alternative to chemical pesticides. A screening of different culture media demonstrated the highest biosurfactant production by L193 in TSB supplemented with colloidal chitin. Surfactants, which are produced in large quantities (2.04 g/L), reduce surface tension to 33 mN/m. Electrospray Q-TOFS MS analysis demonstrated that lipopeptides, such as surfactins, fengycins, bacillomycins and iturins, are the predominant metabolites present in biosurfactants produced by strain L193. Treatment with L193 surfactants led to an aphid mortality rate of 59.8% within 24h. Microscopy analysis showed that these compounds caused insect death by affecting cuticle membranes. An evaluation of aphid feeding activity also demonstrated that aphid feeding capacity is affected by treatment with surfactants. Moreover, microbial cultures of strain L193 and their supernatants also showed high levels of activity against R. padi, which is probably due to the presence of surfactants and hydrolytic enzymes such as proteases and glucanases. This study demonstrates that Bacillus atrophaeus L193 is an effective treatment for plants affected by aphids.